2011
DOI: 10.1038/oby.2011.20
|View full text |Cite
|
Sign up to set email alerts
|

Parental Care in Childhood and Obesity in Adulthood: A Study Among Twins

Abstract: The purpose of the study was to examine if parental antipathy and neglect during childhood were associated with obesity in adulthood. From the Danish Twin Registry (DTR) 146 adult same‐sexed twin pairs discordant for BMI were identified. Criteria for being discordant were that one of the twins should have a BMI between 20 and 25 kg/m2 (normal weight) and the co‐twin a BMI ≥30 kg/m² (obesity). In total 236 out of 289 (81.7%) eligible twin individuals participated in an interview and a physical examination. A pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…This may explain why poor family relations may have a larger effect on obesity for African American females than males [83,84]. More studies have focused on the effect of family function on obesity of adults [16,85] or children [86,87] rather than youth [2]. In a study that used data from the Danish Twin Registry, comparison of same-sexed twin pairs discordant for BMI showed that perceived parental antipathy and neglect predict obesity [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may explain why poor family relations may have a larger effect on obesity for African American females than males [83,84]. More studies have focused on the effect of family function on obesity of adults [16,85] or children [86,87] rather than youth [2]. In a study that used data from the Danish Twin Registry, comparison of same-sexed twin pairs discordant for BMI showed that perceived parental antipathy and neglect predict obesity [16].…”
Section: Discussionmentioning
confidence: 99%
“…More studies have focused on the effect of family function on obesity of adults [16,85] or children [86,87] rather than youth [2]. In a study that used data from the Danish Twin Registry, comparison of same-sexed twin pairs discordant for BMI showed that perceived parental antipathy and neglect predict obesity [16]. Parenting support received from mothers and fathers also have differential effects on the mental health of male and female African American youth [18,74,88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible accounts range from the effects of maternal behavior on gene expression (Weaver et al, 2004) to the influence of maternal behavior on psychological wellbeing of offspring (Bifulco et al, 2005;Camp, 1995;Colletta, 1983;Fergusson and Woodward, 1999;Fisher et al, 2010;Kaess et al, 2013;Vámosi et al, 2011;Whiteside-Mansell et al, 1996). Stress sensitivity may represent a shared pathway for many of these mechanisms, particularly for cognitive-perceptual or psychosis-like outcomes (Collip et al, 2008).…”
Section: Study 1 Discussionmentioning
confidence: 97%
“…It may be that the maternal age association reflects age-related differences in child-rearing practices and behavior, the effects of maternal behavior on gene expression in offspring (Weaver et al, 2004), or factors related to delayed or early motherhood (Ek et al, 2014). Maternal behavior, and antipathy and neglect in particular, is an important predictor of diverse wellbeing outcomes for offspring (Bifulco et al, 2005;Kaess et al, 2013;Vámosi et al, 2011), including psychosis (Fisher et al, 2010). Older maternal age is associated with a more enriched, supportive, and stable environment as well as reduced childhood risk for a variety of problem behaviors (Fergusson and Woodward, 1999).…”
Section: Discussionmentioning
confidence: 98%